The Analysis of the implementation and criticism of the teaching campus program in improving the soft skills of islamic religious education students - Fitriyani Sanuhung; Muh. Wasith Achadi; Nur Ilfi Aisah (At Turots: Jurnal Pendidikan Islam, 2024)
The MBKM policy is one of the policies created by the government, especially the Indonesian education minister, to answer the needs of students in the 4.0 era where technological progress is very rapid. One of the programs of this policy is a teaching campus which provides a platform for students to study and improve their abilities for 4-6 months outside the university or campus environment. This research aims to find out how the teaching campus program is implemented, and also to criticize this program because there are several obstacles that exist in the implementation of the teaching campus program. This research method uses a qualitative method with a critical analysis approach, by collecting data through interviews and documents. The results of the research show that the implementation of the campus teaching program has gone well because from this program students' literacy and numeracy levels have increased, apart from that, students' abilities regarding self-confidence to speak in front of many people have also increased. It's just that there are still several obstacles that occur in the field.